Protective effect of melatonin against Adriamycin-induced cardiotoxicity - ZHANG, YAN (D.A. Spandidos, 2013)
The aim of this in vivo study was to explore the protective properties of melatonin against Adriamycin-induced myocardial toxicity. A rat model of breast cancer was established and the rats were randomly divided into the blank group (Blank), the solvent group [Diss; dehydrated alcohol: physiological saline (1:9)], the Adriamycin group (ADM), the melatonin group (MLT) and the melatonin + Adriamycin group (M+A). The concentrations of lipid peroxide (LPO), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in myocardial tissues were detected, the changes in myocardial tissues were observed using light microscopy and electron microscopy, and the 1-month survival rates of each group of rats were compared. Breast cancer was established in 116 rats. In the ADM group, the concentration of LPO was higher and the concentrations of SOD and GSH-Px were significantly lower than those in the blank group. In the M+A group, compared with the ADM group, the concentration of LPO was lower (P<0.05) and the concentrations of SOD and GSH-Px were higher (P<0.05). It was observed using light and electron microscopy that the myocardial injuries to the M+A group were significantly alleviated in comparison with those in the ADM group; the 1-month survival rate in the M+A group was higher than that in the ADM group. Melatonin may have a protective role in the myocardium by reducing Adriamycin-induced myocardial oxidative damage.